Comparison of genetic diversity of LEP gene between Indonesia domestic goats: Etawa Cross and Senduro Goats - MUHAMMAD FAJAR AMRULLAH; BUDI UTOMO; SUZANITA UTAMA; TITA DAMAYANTI LESTARI; TRI WAHYU SUPRAYOGI; TJUK IMAM RESTIADI; RISTAQUL HUSNA BELGANIA; SUHENDRA PAKPAHAN; ASWIN RAFIF KHAIRULLAH; SHENDY CANADYA KURNIAWAN; OTTO SAHAT MARTUA SILAEN; ABDULLAH HASIB (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Amrullah MF, Utomo B, Utama S, Lestari TD, Suprayogi TW, Restiadi TI, Belgania RH, Pakpahan S, Khairullah AR, Kurniawan SC, Silaen OSM, Hasib A. 2023. Comparison of genetic diversity of LEP gene between Indonesia domestic goats: Etawa Cross and Senduro Goats. Biodiversitas 24: 6567-6573. The leptin (LEP) gene is a gene that functions to produce the hormone leptin secreted by fat tissue that can increase livestock productivity. This study aimed to identify the profile of the LEP gene between Etawah Cross goats and Senduro goats. Gene profiling includes single nucleotide polymorphisms (SNPs) and phylogeny tree reconstruction. Furthermore, 10 whole blood samples from 5 Etawah Cross goats and 5 Senduro goats were collected from goat farms in Lumajang District, Lumajang Regency, Indonesia. The Research procedure involved collecting blood samples, extracting DNA, amplification using the polymerase chain reaction (PCR) method using specific primers, and nucleotide sequencing method. The edited DNA sequences were aligned with some DNA sequences (n=32) of the Capra hircus group published in Genbank. The results of this study obtained the alignment of the LEP gene sequences of Etawah Cross goats and Senduro goats, including T723A, G729A, G758A, A763T, G774C, T1100C, and G1454A. Based on the LEP gene phylogeny tree, Etawah Cross goats and Senduro goats belong to the same clade and have a close kinship with the Bligon goats. The profile of the LEP gene between Etawah Cross goats and Senduro goats varies so that further studies can be carried out to look for the relationship between SNPs and the productivity traits of the LEP gene.